FMEA-Based Risk Assessment in Filter Tank Production - Nina Mahbubah; Dini Fitriani; Abdul Muid (Lamintang Education and Training (LET) Centre, 2025)
Quality assurance is an action to maintain customer satisfaction. As a prominent fabrication producer, Firm A, which receives regular orders from corporate clients, has been challenged with maintaining quality consistency during the production process of filter tanks. This study aims to identify risks and evaluate failures that occur during the filter tank production process based on the Failure Mode and Effects Analysis method. The FMEA stage was started with a walkthrough survey to identify defects, followed by brainstorming sessions with two expert respondents to determine the severity, occurrence, and detection score. Subsequently, the Risk Potential Number score was calculated. Research findings distinguished three types of defects during production stages, namely welding, asymmetric, and painting. Based on risk quantification, it was found that the highest defect score, 392, was attributed to the painting failure category, characterized by excessively thick paint results. This finding was followed by the second-highest score of 336, and the third with value of 294 as failure of asymmetric joints. The practical implication in complementary of the FMEA finding showed that systematic training, audits, and briefings are suggested to address the issues that cause the highest number of failures on fabrication process.